Continuing education program and its relationship with the mental health of engineering faculty members - Nava-Manzo, Josué Omar; Beltran-Sanchez, Jesus Alfonso; González-Treviño, Irma Marcela; Dominguez, Angeles (Frontiers in Education, 2025)
Engineering education is complex and demanding. The COVID-19 pandemic necessitated a sudden shift from face-to-face to virtual teaching modalities, highlighting the need for robust university continuing education programs. This caused professors to invest more hours in attending training, which added to the stressors of the profession and those caused by the global situation and could add to the appearance of mental disorders such as anxiety, depression, stress, or burnout. This research aims to explore the relationship between continuing education programs and the prevalence of mental disorders such as anxiety, depression, stress, and burnout among faculty members. Utilizing a quantitative, non-experimental, cross-sectional, correlational design, the study involved 307 professors from the School of Engineering and Sciences at a private university in northeastern Mexico. Tools included a burnout scale, a stress scale, an anxiety scale, and a self-report depression scale. Findings suggest that faculty members dedicate an average of 20 h per semester to training programs. Although no significant gender differences in training hours were observed, perceived intensity differed with educational level and contract type, suggesting that continuing education programs impact faculty mental health variably. The study concludes a statistically significant relationship exists between stress, anxiety, burnout, and continuing education programs; but the magnitudes are too low to make generalizations. However, it was found that excessive time commitment is a factor that is detrimental to mental health; therefore, it is essential that training programs, in addition to meeting institutional and operational needs, also consider controls that promote the well-being and mental health of teachers. In this sense, continuing education programs contribute to professional growth and can also be a crucial component in the prevention and mitigation of mood disorders among teachers.